Ecotourism for the Sustainability of Protected Areas Soqotra Island Case Study – Yemen - Alokab, Bardees Taher (Journal of Humanities & Social Sciences, 2024)
The study aims to evaluate the role of ecotourism in the conservation and sustainability of the Soqotra Island Reserve and also provides a proposed vision for an ecotourism management plan to achieve sustainable development goals, the researcher adopted qualitative research, the descriptive approach, and a case study approach for the Soqotra Island Reserve has been adopted based on data collection through field visits to Soqotra Island and conducting unstructured interviews, to obtain data from its main source, the purposive sampling method was used to select participants (six managers of offices related to the subject of the study). The study concluded that ecotourism has economic effects it also has a role in the development and sustainability of the Reserve. The study also revealed that internal tourism is considered irresponsible tourism and negatively affects the Reserve, and the study presented a proposed concept for an ecotourism management plan within the Comprehensive Plan, which, if applied, will help achieve the Sustainable Development Goals.
Keywords: Ecotourism; Sustainability; Soqotra; Island; Protected Areas